THE CULTURAL CONCEPTUALISATION OF MANGGARAI PEOPLE ON THE ORIGIN OF LIFE: CULTURAL LINGUISTIC ANALYSIS - Fransiskus Bustan; Agustinus Semiun; Josua Bire (Academic Journal of Educational Sciences, 2020)
This study describes the relationship of between Manggarai language and Manggarai culture, as reflected in the culturalconceptualisation of Manggarai people on the origin of life that includes the origin of human beings, food plants, and animals. The study isviewed from the perspective of cultural linguistics. The study is descriptive. The results of study show that there is a close relationship betweenManggarai language and Manggarai culture, as reflected in the cultural conceptualisation of Manggarai people on the origin of life that includesthe origin of human beings, food plants, and animals.